Knowledge and behavior of elementary school children concerning soil transmitted helminth infections - Annisa Aarts; Ari Budi Himawan; Marloes A van Bokhoven; Job FM Metsemakers; Tri Nur Kristina (Journal of Community Empowerment for Health, 2020)
Soil transmitted helminth infections (STHI) are prevalent among elementary school children in Indonesia. The nutritional impairments that an infection can cause have their consequences for the children’s development and health. This study aimed to determine children’s knowledge and behaviour in relation to the prevalence of STHI among elementary school children in Jepara, a rural regency in Indonesia. The study intended to evaluate the effectiveness of the current elimination program for STHI in this area. A cross-sectional study was conducted among 132 children from eight elementary schools in Mlonggo, Jepara. The research population consisted of children aged eight to ten years old. During September and October 2018, the research population was obtained by consecutive sampling. Information about the children’s knowledge and behaviour regarding STHI was collected using a questionnaire. Stool samples were collected to determine STHI prevalence. Analysis was done using chi-squared and Spearman’s rho tests. Out of 132 children examined, no children had STHI. Scores on STHI knowledge were most often low (51.5%), while scores on behaviour were mostly average (67.4%). Statistical analysis showed that residence was significantly associated with the level of knowledge about STHI (P = 0.007). Additionally, gender (P = 0.002) and a previous STHI (P = 0.041) were significantly associated with the children’s behaviour concerning STHI. This study revealed inadequate knowledge and behaviour concerning STHI in elementary school children in Mlonggo, Jepara. Even though the prevalence of STHI was 0% in the study population, a proper health education program to teach children about STHI is still necessary.